Innovative reutilisation of municipal solid wastes incineration bottom ash as green construction material - Teoh, Peng Jie (2017)
In this study, the aim is to make use of pure Incineration Bottom Ash (IBA) with no other solids, together with alkaline agents to make geopolymer and aerated geopolymer concrete. The IBA has been classified into ferrous materials, non-ferrous materials and glass cullets. The glass cullets in the IBA which has high silicon content will be used as the alumino-silicate oxide for the reaction to form geopolymer binder, while the non-ferrous materials in the IBA provides the source of metallic aluminium. The aluminium produces hydrogen gas upon reaction with alkaline agents and helps to improve the binder stability of geopolymer concrete. IBA from two different plants – Tuas South Incineration Plant (Tuas) and Keppel Seghers Tuas Waste-to-Energy Plant (Keppel) – has been studied and it was found that not all IBA from different plants are suitable for making aerated geopolymer concrete. Non-ferrous materials from Tuas were found to generate lesser aeration as compared to Keppel’s. Since strength and aeration are known to have an inverse relationship in geopolymer concrete, the study focused on developing geopolymer concrete which has high performance using IBA from Tuas and high aeration using IBA from Keppel. Trials have been carried out using Sodium Hydroxide solution as the only alkaline agent. However, it was found that the samples did not gain considerable strength. Hence, Sodium Silicate solution (Waterglass) was introduced as part of the alkaline agents used. Strength is highly dependent on the binder strength that comes from the glass cullets, while aeration depends on the amount of metallic alumina in the non-ferrous materials. Thus, trials with varying Waterglass and Sodium Hydroxide ratio were carried out on grinded glass, Tuas non-ferrous materials and Keppel non-ferrous materials to find the best ratio to achieve high strength and aeration. The Waterglass: Sodium Hydroxide ratio of 5:1 and 2:1 were determined to be the best for achieving high strength (thus, performance) and aeration respectively. Subsequently, by varying the dosage of non-ferrous materials in each mix, it was found that a range of samples with compressive strength 20.7MPa - 64.5MPa was possible for high performance concrete and 2.3MPa (0.77g/cm³) - 10.4MPa (1.13g/cm³) was possible for high aeration concrete. The binder stability for high performance concrete samples had also improved with the addition of non-ferrous materials as compared to samples made from 100% glass.